Killian-Jamieson diverticulum safely resected using a manual intraoperative neural monitoring system: a case report - Ryo Ataka; Shigeru Tsunoda; Saori Goto; Tatsuto Nishigori; Shigeo Hisamori; Kazutaka Obama; Yoshiharu Sakai (Surgical Case Reports)
Abstract Background Killian-Jamieson diverticulum is a rare pharyngoesophageal diverticulum. The risk of intraoperative injury of the recurrent laryngeal nerve (RLN) is high during surgical resection of Killian-Jamieson diverticulum because the RLN usually runs next to the base of the diverticulum. We present a case of Killian-Jamieson diverticulum that was safely resected with effective use of an intraoperative nerve monitoring (IONM) system with a handheld stimulating probe to prevent RLN injury. Case presentation A 69-year-old man complaining of dysphagia was diagnosed with Killian-Jamieson diverticulum and underwent open transcervical diverticulectomy. Because the anterior aspect of the diverticulum was expected to be close to the RLN, the accurate location of the RLN was checked during dissection by intermittent stimulation using a handheld probe of the IONM system to avoid mechanical and thermal injury. The diverticulum was transected longitudinally using a linear stapler, and the staple line was buried using absorbable sutures from the distal end. During its closure, RLN was identified very close to the diverticulum stump by IONM, and the upper side of the stump was left unburied to avoid RLN injury. The postoperative course was uneventful and the patient was discharged on postoperative day 7. Postoperative evaluation showed no vocal cord paralysis. Conclusion IONM may be beneficial during open surgery for Killian-Jamieson diverticulum, which usually protrudes just lateral to the RLN.